GROSS AND MICROSCOPIC SKIN THICKNESS OF RED SOKOTO GOAT ECOTYPES - Umar A.A.; Atabo S.M. (IJRDO-Journal of Applied Science, 2020)
Gross and microscopic skin thickness of the red Sokoto goat were determined. The skin was found to contain two layers; the epidermis and the dermis, in the selected body regions (lateral neck, rump, mid-side, thigh and scrotum in males or udder in females) of the five identified ecotypes of red Sokoto goat. The epidermis contributed 1.85-3.07% while dermis contributed between 96.93-98.15% of the total skin thickness. The skin thickens with age in both males and females. However, males have a thicker skin than the females in all the five ecotypes and the skin from the dark red ecotypes was found to have greater thickness (P≤0.05) than skins from other ecotypes, with light brown coat colour skin having the least thickness. Skins with high thickness like the dark red ecotypes are most preferred in the leather industries. The thickness of the skin based on the body regions showed greater thickness at rump and least thickness at lateral mid-side. The scrotum and udder were found to be generally thin when compared with other body regions. The gross and microscopic skin thickness of the red Sokoto goat ecotypes can serve as a measure to determine leather quality